2018
DOI: 10.1186/s13023-018-0946-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of low-dose Sirolimus in Lymphangioleiomyomatosis

Abstract: BackgroundLymphangioleiomyomatosis is a rare disease caused by unregulated activation of mammalian target of rapamycin (mTOR) signalling pathway. Sirolimus showed efficacy in a phase 3 trial of patients with lymphangioleiomyomatosis, but the optimal dose remains unclear.MethodsWe investigated the efficacy and safety of low-dose compared with conventional-dose sirolimus. Clinical data of 39 patients with lymphangioleiomyomatosis (mean age, 34.8 years; median treatment period, 29.6 months) who received sirolimus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Ando et al (2013) showed an improvement in the function of the respiratory system and withdrawal of lymph exudates in patients treated with low doses, to a degree comparable with the results of trials using the higher dose [10]. However, Yoon et al (2018) showed lower effectiveness of lower doses of sirolimus, whose use at the same time did not lead to a decreased frequency of undesirable adverse effects [97]. In a meta-analysis by Gao et al (2018), encompassing 7 clinical trials concerning the use of sirolimus in LAM, a significant improvement of FEV 1 and FVC was confirmed in treated patients -the weighted average of differences was: 0.15 l (95% CI: 0.08-0.22, p < 0.01, I 2 = 0%) for FEV 1 and 0.22 l (95%: 0.11-0.32, p < 0.01, I 2 = 0%) for FVC [98].…”
Section: Pulmonary Lam Treatmentsupporting
confidence: 61%
See 1 more Smart Citation
“…Ando et al (2013) showed an improvement in the function of the respiratory system and withdrawal of lymph exudates in patients treated with low doses, to a degree comparable with the results of trials using the higher dose [10]. However, Yoon et al (2018) showed lower effectiveness of lower doses of sirolimus, whose use at the same time did not lead to a decreased frequency of undesirable adverse effects [97]. In a meta-analysis by Gao et al (2018), encompassing 7 clinical trials concerning the use of sirolimus in LAM, a significant improvement of FEV 1 and FVC was confirmed in treated patients -the weighted average of differences was: 0.15 l (95% CI: 0.08-0.22, p < 0.01, I 2 = 0%) for FEV 1 and 0.22 l (95%: 0.11-0.32, p < 0.01, I 2 = 0%) for FVC [98].…”
Section: Pulmonary Lam Treatmentsupporting
confidence: 61%
“…In an observational trial by Taveira-DaSilva et al (2011) planned to evaluate the benefit of using sirolimus in patients with a severe course of LAM and abundant lymph exudates in the pleural cavity in all 12 patients a complete or almost complete reduction of the volume of the accumulating liquid took place which allowed draining of the pleural cavity to be stopped in 2 of them [84]. In two retrospective analyses the effectiveness of sirolimus at a lower dose (target drug concentration in serum below 5 ng/m) in comparison with a standard dose (drug concentration in serum 5-15 ng/mL on the basis of the MILES trial), was evaluated, yielding contradictory results [10,97]. Ando et al (2013) showed an improvement in the function of the respiratory system and withdrawal of lymph exudates in patients treated with low doses, to a degree comparable with the results of trials using the higher dose [10].…”
Section: Pulmonary Lam Treatmentmentioning
confidence: 99%
“…This is important because chronic rapamycin administration negatively regulates mTORC2 [125,126]. Additional off-target side effects of longerterm mTOR (mTORC1 and 2) inhibition using rapamycin include decreased insulin sensitivity, glucose intolerance, early onset diabetes, and hyperlipidemia, which have been linked to the diminished mTORC2-mediated Akt phosphorylation [127] [128]. Collectively, negative off-target effects of chronic mTOR inhibition using rapamycin likely outweigh the cardiovascular benefits.…”
Section: Pharmacological and Nutraceutical Interventionsmentioning
confidence: 99%
“…The stent was approved by the US FDA in 2003 (Cypher ® , Johnson & Johnson) [ 10 ]. In 2015, sirolimus became the first drug approved by the US FDA for the treatment of lymphangioleiomyomatosis (LAM), a rare, progressive, cystic lung disease associated with inappropriate activation of mTOR signaling [ 11 , 12 , 13 ]. In addition, sirolimus is a potential treatment therapy for lupus [ 14 ], lymphatic malformation [ 15 ], skin cancer [ 16 ], and lung cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%